Growth in atopic eczema: a controlled study by questionnaire. Issue 11 (November 1989) - Pike, M G; Chang, C L; Atherton, D J; Carpenter, R G; Preece, M A
Abstract : The parents of 128 children with atopic eczema and 117 healthy control children responded to a questionnaire that included measurement of their own and their children's heights at home after standardised instructions. When cases and controls were compared there was no significant difference in parental height but the children with eczema were significantly shorter than the healthy control group. This difference remained significant when children with associated asthma were excluded from the analysis.